ANALISIS PENGARUH REPEAT ORDER, PELABELAN HALAL, DAN PEREKRUTAN MEMBER TERHADAP VOLUME PENJUALAN PADA PT. ORINDO ALAM AYU CABANG YOGYAKARTA - Aini, Laila Nur; Rohwiyati, Rohwiyati (Universitas Of Surakarta, 2021)
In this study the authors have the aim to determine the effect of repeat orders, halal labeling and member recruitment on sales volume at PT. Orindo Alam Ayu Yogyakarta Branch, both partially and simultaneously. The data needed in this study is primary data. Primary data obtained by the questionnaire method of a sample of 100 respondents. Analysis of the data used in this research is multiple linear regression test, t test, F test and coefficient of determination test. The results of data analysis in this study can be concluded that repeat orders, halal labeling and member recruitment have a positive and significant effect on sales volume at PT. Orindo Alam Ayu Yogyakarta Branch.